Microclimate Characteristics On Oil Palm (Elaeis guineensis Jacq.) And Agarwood (Aquilaria malaccensis Lamrk.) Agroforestry System - Budi Mulyono; Nurul Qomar; Wawan Wawan (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2022)
In general, oil palm plants are cultivated using a monoculture system. The monoculture system is profitable from an economic perspective and harms the environment; one is the microclimate. One of the efforts to reduce the negative impact of the oil palm monoculture system is to apply the oil palm agroforestry system with agarwood. This research is conducted on smallholder oil palm plantations in Bukit Kemuning Village, Tapung Hulu Sub District, Kampar District, Riau Province. This research was conducted using a survey method, which was done by choosing a location intentionally. Determination of the research location using purposive sampling method, that is, on land found agroforestry systems of oil palm plants with agarwood and oil palm monoculture systems in the same location. Microclimate observations are carried out by measuring air temperature, air humidity, and sunlight intensity. Measurement of air temperature and humidity uses the Temperature and Humidity Data Logger, while the sunlight intensity measurement uses the Lux Meter Data Logger tool. Measurements are carried out one day a week for three months, for getting 12 times of data retrieval. The recording is carried out from 07.00 am to 05.00 pm, with 15 minutes intervals. Microclimate data on agroforestry and monoculture systems are analyzed in comparative descriptive analysis. Based on the results of the study, it is concluded that the microclimate in the agroforestry system of oil palm and agarwood was better than that of the oil palm monoculture system, where the light intensity and air temperature in the agroforestry system are lower than the monoculture system, and the humidity in the agroforestry system higher than the monoculture system. In general, oil palm plants are cultivated using a monoculture system. Monoculture system is profitable from an economic perspective, but also has a negative impact on the environment, one of which is the micro climate. One of the efforts to reduce the negative impact of the oil palm monoculture system is to apply the oil palm agroforestry system with gaharu. This research is conducted on smallholder oil palm plantations in Bukit Kemuning Village, Tapung Hulu Sub District, Kampar District, Riau Province. This research is conducted using a survey method. Determination of the research location using purposive sampling method, namely on land found agroforestry systems of oil palm plants with gaharu and oil palm monoculture systems in one stretch. Microclimate observations are carried out by measuring air temperature, air humidity, and sunlight intensity. Measurement of air temperature and humidity uses the Temperature and Humidity Data Logger, while the measurement of sunlight intensity uses the Lux Meter Data Logger tool. Measurements are carried out one day a week for 3 months, for getting 12 times of data retrieval. Recording is done at 07.00 am up to 05.00 pm with 15 minute intervals. Microclimate data on agroforestry and monoculture systems are analyzed in comparative descriptive analysis. Based on the results of the study, it is concluded that the microclimate in the agroforestry system of oil palm and gaharu was better than that of the oil palm monoculture system, where the light intensity and air temperature in the agroforestry system are lower than the monoculture system, and the humidity in the agroforestry system higher than the monoculture system